Struggle Outside Jails: Scoping Review of Impacts and Resiliency Among Children of Incarcerated Parents - Ghina Syauqila; Dian Veronika Sakti Kaloeti (Universitas Ahmad Dahlan, 2024)
Parental incarceration has a significant impact on children, so resiliency is the essential thing that needs to be owned to minimize this impact. However, research on this matter is still very limited. This scoping review aims to explore the impact and resilience of children with incarcerated parents. PRISMA and five databases (Scopus, ScienceDirect, EBSCOhost, Semantic Scholar, and Springer) were used in this study. There were ten articles that met the inclusion criteria. The results have shown that parental incarceration leads to mental health problems, behavior problems, decreased academic performance, family dysfunction, and financial hardship. Social support and children’s involvement in positive activities will help the resilience process. Future research can focus on the dynamics of resilience by considering the stages of development and cultural context, as well as its relation to preventive, intervention, and rehabilitation efforts for children with incarcerated parents, especially in Indonesia.